INTENSI MEMBELI DITINJAU DARI PERSEPSI KONSUMEN TERHADAP KUALITAS PRODUK - Endah Mudjiasih; Ika Febrian Kristiana (Jurnal Bisnis dan Ekonomi, 2010)
Intention to buy is not new in studies of consumer psychology. interpreted as an intention tobuy an estimate / prediction products to be purchased by consumers (Mowen & Minor, 2002: 322),would be attractive for producers to know what things are also affected, including localmanufacturers, one of which SMEs. However, the proliferation of persuasion to use local productsand the proliferation of SMEs as one of the producers turned out to show the contradictoryconditions. Performer MSME precisely main constraints facing competition from imported productsdue to low quality of their products. Assessment of a better quality product from the forming of aperson's perception is based on the product. Perceptions of the quality of a product can mean theoverall assessment of the consumer, which involves a process of cognitive, affective, and konasi tothe functions and advantages of products produced by manufacturers. Quality products that satisfyconsumers encouraged to bond the relevant product (Kotler and Armstrong, 1999: 354).Keywords: intention to buy, consumer’s perception, quality product